Simultaneous Visualization of 161Tb- and 177Lu-Labeled Somatostatin Analogues Using Dual-Isotope SPECT Imaging - Francesca Borgna; Patrick Barritt; Pascal V. Grundler; Zeynep Talip; Susan Cohrs; Jan Rijn Zeevaart; Ulli Köster; Roger Schibli; Nicholas P. van der Meulen; Cristina Müller (MDPI AG, 2021)
The decay of terbium-161 results in the emission of β¯-particles as well as conversion and Auger electrons, which makes terbium-161 interesting for therapeutic purposes. The aim of this study was to use dual-isotope SPECT imaging in order to demonstrate visually that terbium-161 and lutetium-177 are interchangeable without compromising the pharmacokinetic profile of the radiopharmaceutical. The 161Tb- and 177Lu-labeled somatostatin (SST) analogues DOTATOC (agonist) and DOTA-LM3 (antagonist) were tested in vitro to demonstrate equal properties regarding distribution coefficients and cell uptake into SST receptor-positive AR42J tumor cells. The radiopeptides were further investigated in AR42J tumor-bearing nude mice using the method of dual-isotope (terbium-161/lutetium-177) SPECT/CT imaging to enable the visualization of their distribution profiles in the same animal. Equal pharmacokinetic profiles were demonstrated for either of the two peptides, irrespective of whether it was labeled with terbium-161 or lutetium-177. Moreover, the visualization of the sub-organ distribution confirmed similar behavior of 161Tb- and 177Lu-labeled SST analogues. The data were verified in quantitative biodistribution studies using either type of peptide labeled with terbium-161 or lutetium-177. While the radionuclide did not have an impact on the organ distribution, this study confirmed previous data of a considerably higher tumor uptake of radiolabeled DOTA-LM3 as compared to the radiolabeled DOTATOC.